Effects of Storage Conditions on Consumer and Chemical Assessments of Raw 'Nonpareil' Almonds Over a Two‐Year Period. Issue 3 (22nd January 2018) - Pleasance, Emily A.; Kerr, William L.; Pegg, Ronald B.; Swanson, Ruthann B.; Cheely, Anna N.; Huang, Guangwei; Parrish, Daniel R.; Kerrihard, Adrian L.
Abstract : Abstract: Raw almonds are a major commodity, yet much is unknown about how storage conditions determine their shelf life. The storage stability, as measured by consumer assessments and chemical measures, of raw almonds was determined for samples stored in cardboard boxes and polypropylene packaging for 2 years at 4, 15, 25, and 35 °C, and at 50% and 65% relative humidity (RH). Samples stored in unlined cartons always failed (>25% rejection) before their counterparts stored in polypropylene bags under identical environmental conditions. Models determined that polypropylene packaging (as opposed to unlined cardboard cartons) extended the time until sample rejection by more than 7 months. Temperature and RH were both negatively associated with storage time until failure. Flavor was a greater contributor to consumer acceptability than texture or odor, while peroxide values and free fatty acids were of greater importance in predicting raw almond consumer quality than measures of conjugated dienes or 2‐thiobarbituric acid‐reactive substances. Practical Application: The results of this study will allow almond producers to determine packaging types and environmental storage conditions that provide shelf life of a specified time.